Rights and Courts in Pursuit of Social Change : legal mobilisation in the multi-level European system - Anagnostou, Dia (Oñati international series in law and society., 2014)
This book explores the relationship between law, rights and social mobilisation in Europe, and examines the ways in which legal processes are mobilised by less privileged social actors to advance their rights claims and pursue social change.